Optimizing of Public Housing Financing Policies for Low Income Community in Indonesia : Conceptual Approach. - Wahyudi, Noeroso L. (Archives of Business Research, 2019)
Evolution on housing finance policies and development of public housing for low income community (MBR) are interesting phenomenon which have inspired a study to optimize its financing strategically. Conceptually, there are two approaches on analyzing on public housing financing policies for MBR, namely: i) the market or supply chain approach, and ii) good governance approach. Market approach is focusing on business supply chain between actors interaction in demand and supply responively. While the approach of good governance or partnership is the interaction among the stakeholders (stakeholders), especially between the agent or regulator with the actors or operators in executing to promote housing development towards more credible and adaptive. This good governance approach is deeply explored in the partnership among financial institutions such as banking, insurance. . To get the findings and recommendations, this paper explores a reference not only on theoretical study, potential financing based on the existing legal basis of potential funding sources qualitively. The next exploration are the developments in the availability of housing for MBR. Analysis of housing finance optimally explores on three (3) sub-topics, namely: i) the target housing finance MBR, ii) the establishment center of revolving fund institution (PPDPP), iii) Secondary Financing Company (PT SMF). Hopefully, implementing these concept could promote public housing development more conducive resulted in less shortage or backlog of apropriate public house for low income society in Indonesia.